Familiarity, but not Recollection, Supports the Between-Subject Production Effect in Recognition Memory. - Fawcett, Jonathan M.; Ozubko, Jason D. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2016)
Five experiments explored the basis of the between-subjects production effect in recognition memory as represented by differences in the recollection and familiarity of produced (read aloud) and nonproduced (read silently) words. Using remember-know judgments (Experiment 1b) and a dual-process signaldetection approach applied to confidence ratings (Experiments 2b and 3), we observed that production influences familiarity but not recollection when manipulated between-subjects. This is in contrast to within-subject designs, which reveal a clear effect of production on both recollection and familiarity (Experiments 1a and 2a). Our findings resolve contention concerning apparent design effects: Whereas the within-subject production effect is subserved by separable recollective- and familiarity-based components, the between-subjects production effect is subserved by the familiarity-based component alone. Our findings support a role for the relative distinctiveness of production as a means of guiding recognition judgments (at least when manipulated within-subjects), but we also propose that production influences the strength of produced items, explaining the persistence of the effect in between-subjects designs.